EFISIENSI APLIKASI PUPUK KIESERITE UNTUK MENINGKATKAN SERAPAN HARA DAN PRODUKSI JAGUNG MANIS - Ishaq, Rizki Maulana; Putri, Fenalda Sekar Maretha; Kurniawan, Syahrul; Hidayat, Muhamad Taufiq; Albarki, Georona Kusuma (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Sweet corn production in Batu city is lower than in other districts/cities. This is thought to be due to a decrease in land area and deterioration of land conditions. In addition, intensive agricultural practices in the long term can reduce soil pH which will have an impact on the low availability of essential nutrients such as Mg, S, and P. Kieserite fertilizer application can be used as an effort to overcome these problems. This study aimed to evaluate the application of various doses of kieserite fertilizer combined with a single inorganic fertilizer on the efficiency of nutrient uptake and production of sweet corn plants. The research was conducted in Junrejo Village, Batu City in September 2023 - May 2024. The research used Randomized Group Design (RGD) with Kieserite fertilizer doses (0; 26.92; 53.85; 80.77 kg ha-1). The parameters observed and analyzed were plant height and number of leaves, corn production (quantity and quality), soil chemical properties (pH, Mg-dd, SO42-, P-available), nutrient uptake efficiency (Mg, S, P), and phosphate solubilizing bacteria (BPF) population. The research data were analyzed by ANOVA then DMRT further test at 5% level, correlation and regression tests using R-Studio. The results showed that the application of Kieserite fertilizer at a dose of 50% ( 26.92 Mg ha-1) combined with inorganic fertilizer (N,P,K) at a dose of 75% shown in treatment A6 significantly increased the efficiency of Mg nutrient uptake by (RE=7.7%), S nutrient by (RE=2.9%), and P nutrient by (RE=49.9%). This increase in nutrient uptake efficiency certainly affected the level of sweet corn productivity. The correlation test between nutrient uptake efficiency (Mg, S, and P) and sweet corn production showed a positive and strong relationship (r=0.5-0.7), where the higher the nutrient uptake efficiency, the higher the sweet corn production. This study confirms the importance of efficient use of Kieserite fertilizer in order to get optimum production results.